A nickel-based catalyst for methanation of carbon monoxide and carbon dioxide and a preparation method thereof
By using amorphous Al2O3-ZrO2 composite oxide support and multi-interface system Ni-NiAl2O4/Al2O3-ZrO2 catalyst, the existing catalysts have been solved, and the problem of insufficient low-temperature activity and poor high-temperature stability in CO and CO2 methanation reactions is achieved, and high Conversion rate and high selectivity methanation reaction effect.
Patent Information
- Application Number
- CN202211704567.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The existing catalysts have problems of insufficient low-temperature activity and poor high-temperature stability in the CO and CO2 methanation reaction, resulting in kinetic limitation and loss of activity.
Amorphous Al2O3-ZrO2 composite oxide is used as a support to induce the phase transformation of Al2O3 and ZrO2 by changing the calcining temperature to form a multi-interface system Ni-NiAl2O4/Al2O3-ZrO2 catalyst, which improves the low-temperature activity and high-temperature stability of the catalyst.
It achieves high conversion of CO and CO2 and high selectivity of CH4, and the catalyst exhibits excellent stability and activity at high temperatures, which is suitable for industrial-scale production.
Smart Images

Figure CN115888724B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of CO methanation and CO2 methanation catalysts, and in particular to a nickel-based catalyst for methanation of carbon monoxide and carbon dioxide and a preparation method thereof. Background Art
[0002] Due to the large amount of anthropogenic CO2 emissions generated by the combustion of fossil fuels, the current concentration of CO2 in the atmosphere is at an all-time high, causing widespread environmental problems such as global warming, climate change and ocean acidification. In recent decades, the utilization of CO2 has attracted great attention worldwide. The technology of converting CO2 into methane can not only produce the currently urgently needed natural gas, but also serve as a suitable energy storage carrier to regulate the fluctuations of solar and wind energy and stabilize the power grid. It is an effective way to utilize CO2 resources.
[0003] The production of synthetic natural gas from coal through synthesis gas (a mixture of carbon monoxide and hydrogen) is also one of the important ways to utilize coal efficiently, cleanly and efficiently. It can optimize my country's energy structure of "rich in coal and less in gas", and is of great significance for alleviating my country's natural gas shortage and ensuring energy security. In addition, other coal chemical processes will also produce a large amount of pyrolysis gas and raw coal gas containing CO and H2. Producing natural gas through CO methanation reaction of this by-product gas is of great significance to improving coal utilization.
[0004] Both CO and CO2 methanation are exothermic reactions. However, due to kinetic limitations, CO and CO2 activation requires higher temperatures. Therefore, it is very necessary to develop a catalyst with low-temperature activity and high-temperature stability.
[0005] The catalyst carrier not only strongly affects the dispersion of nickel metal, but also has a great influence on the adsorption and activation of CO and CO2. Many oxide carriers, such as SiO2, MgO, TiO2, CeO2 or their composite oxides, have been used for Ni catalysts in methanation. However, Ni has poor stability on these carriers and is easily sintered under high temperature conditions, causing the catalyst to lose activity or cause carbon deposition. During the research process of our research group, it was found that in the methanation reaction, the Al-Zr composite oxide carrier showed better activity, selectivity and stability than the Ni / Al2O3 catalyst. However, Al2O3 and ZrO2 will undergo different crystal phase transformations during the calcination process. How to reasonably control the preparation conditions and prepare Al2O3 and ZrO2 composite oxide-loaded Ni-based catalysts with low-temperature activity and high-temperature stability has become a problem that needs to be solved. Summary of the invention
[0006] Based on the above technical problems, the present invention provides a nickel-based catalyst for the methanation of carbon monoxide and carbon dioxide, which is an amorphous Al2O3-ZrO2 composite oxide as a carrier, and the calcination temperature is changed to induce a phase transition between Al2O3 and ZrO2. The phase transfer during the calcination process of the Ni-Al-Zr ternary system is utilized to form a multi-interface system of Al-O-Ni, Ni-O-Zr and Al-O-Zr on the catalyst, and a Ni-NiAl2O4 / Al2O3-ZrO2 catalyst is formed after reduction.
[0007] Among them, Al2O3 and NiAl2O4 can provide medium-strength adsorption sites for CO2. The coexistence of the two leads to a strong dissociation ability of the active sites. Therefore, the CO2 methanation reaction can be achieved by coupling the reverse water gas shift reaction (RWGS) with CO methanation. The CO* reaction intermediate is generated by the RWGS reaction. Then, in the dispersed Ni 0 CO methanation reaction is carried out on the surface to generate CH4. In addition, the rich multi-interface system also inhibits the sintering process; therefore, the methanation catalyst prepared by the present invention has high conversion rate of CO and CO2 and CH4 selectivity, stable performance, and excellent utilization prospects.
[0008] The specific preparation scheme is as follows:
[0009] A method for preparing a nickel-based catalyst for methanation of carbon monoxide and carbon dioxide comprises the following steps:
[0010] Step 1: Preparation of Al2O3-ZrO2 composite oxide carrier:
[0011] (1) Weigh 73.5838 g aluminum nitrate nonahydrate, 13.0762 g zirconium oxychloride octahydrate, 11 g template, 10 ml PEG400, 20 g PEG2000, and 100 ml ethanol, dissolve in 400 ml distilled water, and stir magnetically for about 50-70 min to prepare a composite solution;
[0012] (2) Slowly adding NH3·H2O to the composite solution by titration and continuously stirring until the pH value is 7.5-8.5 to obtain a white precipitate; the NH3·H2O is a precipitant;
[0013] (3) Continue stirring for 100-140 minutes and then let stand and age for 11-13 hours;
[0014] (4) The precipitate was centrifuged and filtered and washed 2-4 times with distilled water and ethanol respectively until no chloride ions could be detected with silver nitrate;
[0015] (5) Dry the obtained precipitate in a drying oven at 70°C-90°C for 10h-14h, then adjust the temperature to 110°C-130°C and continue drying for 10h-14h;
[0016] (6) After drying, the obtained solid was crushed, transferred to a muffle furnace, heated to 300-400°C at a heating rate of 0.9°C / min-1.1°C / min for 100-140 min, and then calcined at 600°C for 4.5h-5.5h to obtain an Al2O3-ZrO2 composite carrier;
[0017] Step 2: Preparation of methanation catalyst product:
[0018] (1) Weigh 0.9733 g of nickel nitrate hexahydrate, add it to 2.0 ml of distilled water and stir until it is completely dissolved to prepare a nickel nitrate solution;
[0019] (2) Weigh 0.75 g of Al2O3-ZrO2 amorphous composite oxide and add it to the nickel nitrate solution, mix well and let stand for 5.5 h to 6.5 h;
[0020] (3) Dry the obtained sample in a drying oven at 100°C-120°C for 10h-14h, then heat it to 600°C-800°C in a muffle furnace at a heating rate of 0.9°C / min-1.1°C / min, and calcine it for 4.5h-5.5h to obtain a finished methanation catalyst.
[0021] Furthermore, a method for preparing a carbon monoxide methanation catalyst and a carbon dioxide methanation catalyst comprises the following steps:
[0022] Step 1: Preparation of Al2O3-ZrO2 composite carrier:
[0023] (1) Weigh 73.5838 g aluminum nitrate nonahydrate, 13.0762 g zirconium oxychloride octahydrate, 11 g template, 10 ml PEG400, 20 g PEG2000, and 100 ml ethanol, dissolve in 400 ml distilled water, and stir magnetically for about 60 min to prepare a composite solution;
[0024] (2) Slowly adding NH3.·H2O to the composite solution by titration and continuously stirring until the pH value reaches 8, and a white precipitate is obtained; the NH3·H2O is a precipitant;
[0025] (3) Continue stirring for 120 min and then let stand and age for 12 h;
[0026] (4) The precipitate was centrifuged and filtered and washed three times with distilled water and ethanol respectively until no chloride ions could be detected with silver nitrate;
[0027] (5) The obtained precipitate was first dried in a drying oven at 80°C for 12 hours to slowly remove surface water and prevent the water from evaporating too quickly and bringing salt out of the pores of the catalyst carrier to cause surface enrichment; the temperature was then adjusted to 120°C and continued to be dried for 12 hours to remove crystallization water and ensure that the water was dried before calcination to avoid structural collapse during the calcination process;
[0028] (6) After drying, the obtained solid was crushed, transferred to a muffle furnace, heated to 350°C at a heating rate of 1.0°C / min, and calcined for 120 min, followed by calcination at 600°C for 5 h to obtain an Al2O3-ZrO2 composite carrier;
[0029] Step 2: Preparation of methanation catalyst product:
[0030] (1) Weigh 0.9733 g of nickel nitrate hexahydrate, add it to 2.0 ml of distilled water and stir until it is completely dissolved to prepare a nickel nitrate solution;
[0031] (2) Weigh 0.75 g of Al2O3-ZrO2 composite carrier and add it to nickel nitrate solution, mix well and let stand for 6 hours;
[0032] (3) The obtained sample was dried in a drying oven at 110° C. for 12 h, and then heated to 700° C. in a muffle furnace at a heating rate of 1.0° C. / min and calcined for 5 h to obtain a finished methanation catalyst.
[0033] Furthermore, the template is P123.
[0034] Furthermore, aluminum nitrate nonahydrate, zirconium oxychloride octahydrate, and nickel nitrate hexahydrate were all analytically pure.
[0035] Furthermore, NH3·H2O was slowly titrated into the composite solution using NH3·H2O as a precipitant, and the mixture was continuously stirred at a rate of 800 r / min in a 70 °C water bath;
[0036] Furthermore, the composite salt concentration of the composite solution is 0.4 mol / L-0.6 mol / L.
[0037] On the other hand, the present invention also provides a nickel-based catalyst for the methanation of carbon monoxide and carbon dioxide, the catalyst comprising an active component and a carrier, the active component being Ni, the carrier being an amorphous aluminum-zirconium composite oxide, the mass percentage content of the active component as NiO being 24-26wt%, and the rest being the carrier.
[0038] Furthermore, the mass percentage content of the active component in terms of NiO is 25wt%, and the amorphous aluminum-zirconium composite oxide is an Al2O3-ZrO2 composite carrier.
[0039] Furthermore, the mass ratio of Al2O3 to ZrO2 in the Al2O3-ZrO2 composite carrier is 2:1. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 1 is the XRD diagram of the carrier obtained in Example 3 of the present invention and the N / AZ600, N / AZ700 and N / AZ800 catalysts;
[0041] Figure 2 is the HAADF-STEM image of N / AZ600 catalyst;
[0042] Figure 3 is the HAADF-STEM image of N / AZ700 catalyst;
[0043] Figure 4 is the HAADF-STEM image of N / AZ800 catalyst;
[0044] Figure 5 It is the graph of carbon dioxide conversion rate of N / AZ600, N / AZ700 and N / AZ800 catalysts;
[0045] Figure 6 is the CO2 selectivity diagram of N / AZ600, N / AZ700 and N / AZ800 catalysts;
[0046] Figure 7 This is the stability test chart of N / AZ700 catalyst;
[0047] Figure 8 This is the TG-DTG graph of N / AZ700 catalyst after stability test;
[0048] Fig. 9 HAADF-STEM and EDX element distribution map after catalyst reduction;
[0049] Fig.10 is the CO2 methanation activity of the used N / AZ700 catalyst: CO2 conversion rate;
[0050] Fig.11 is the CO2 methanation activity of the used N / AZ700 catalyst: CH4 selectivity;
[0051] Fig.12 is the XRD spectrum of the used N / AZ700 catalyst;
[0052] Fig.13 HAADF-STEM and element distribution map of N / AZ700 catalyst;
[0053] Fig.14 is CO methanation activity: CO conversion rate;
[0054] Fig.15 is CO methanation activity: CH4 selectivity;
[0055] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0056] 1. The present invention uses a method of changing the calcination temperature to induce the phase transition of Al2O3 and ZrO2, and utilizes the phase transfer during the calcination process of the Ni-Al-Zr ternary system to form a multi-interface system of Al-O-Ni, Ni-O-Zr and Al-O-Zr on the catalyst, and forms a Ni-NiAl2O4 / Al2O3-ZrO2 catalyst after reduction; wherein Al2O3 and NiAl2O4 can provide medium-strength adsorption sites for CO2, and the coexistence of the two results in a strong dissociation ability of the active sites; therefore, the CO2 methanation reaction can be achieved by coupling the reverse water gas shift reaction (RWGS) with CO methanation; CO* reaction intermediates are generated by the RWGS reaction. Then, in the dispersed Ni 0 CO methanation reaction is carried out on the surface to generate CH4. In addition, the rich multi-interface system also inhibits the sintering process; therefore, the methanation catalyst prepared by the present invention has high conversion rate of CO and CO2 and CH4 selectivity, stable performance, and excellent utilization prospects.
[0057] 2. The catalyst preparation method of the present invention is simple, the preparation process is simple, the operating conditions are flexible, and it is easy to repeat. In addition, the raw materials used are widely available, cheap, and suitable for large-scale production.
[0058] 3. The catalyst prepared by the technical solution of the present invention has high CO2 activity and good selectivity at high temperature. −1 ∙h −1 When the temperature is 400℃, the CO2 conversion rate reaches 87%, the selectivity reaches 100%, and no obvious deactivation is observed after a long reaction time of 138h.
[0059] 4. The present invention overcomes the shortcomings of the prior art. During the calcination process, the temperature is gradually increased at a heating rate of 0.9°C / min-1.1°C / min, and the crystal transformation of the carrier is utilized, resulting in the redispersion of Ni and Al2O3 on the surface of the carrier. While improving the dispersion, the interaction between Ni and the carrier is also increased, thereby showing good activity and high thermal stability.
[0060] 5. The Al2O3-ZrO2 composite carrier prepared by the present invention, the composite oxide material Al2O3 and the composite oxide of ZrO2, due to the combination of the large surface area of Al2O3 and the excellent thermal stability and chemical stability of ZrO2, is suitable as a carrier of Ni-based CO2 methanation catalyst, laying a foundation for the technology of converting CO2 into methane, and also recycling CO2 resources, which is environmentally friendly and economical.
[0061] 6. The catalyst prepared by the present invention is 3.0MPa and the air velocity is 15000 ml∙g −1 ∙h −1 It exhibits excellent CO methanation performance under high pressure and high space velocity. DETAILED DESCRIPTION
[0062] Example 1
[0063] A method for preparing an Al2O3-ZrO2 composite carrier comprises the following steps:
[0064] (1) Weigh 73.5838 g aluminum nitrate nonahydrate, 13.0762 g zirconium oxychloride octahydrate, 11 g template, 10 ml PEG400, 20 g PEG2000, and 100 ml ethanol, dissolve in 400 ml distilled water, and stir magnetically for about 50 min to prepare a composite solution;
[0065] (2) Using NH3·H2O as a precipitant, slowly titrate NH3·H2O into the composite solution and continue stirring until the pH reaches 7.5 to obtain a white precipitate;
[0066] (3) Continue stirring for 100 min and then let stand and age for 16 h;
[0067] (4) The precipitate was centrifuged and filtered and washed twice with distilled water and ethanol respectively until no chloride ions could be detected with silver nitrate;
[0068] (5) Dry the obtained precipitate in a drying oven at 70°C for 10 h, then adjust the temperature to 110°C and continue drying for 10 h;
[0069] (6) After drying, the obtained solid was crushed, transferred to a muffle furnace, heated to 300-400°C at a heating rate of 0.9°C / min for 100-140min, and then calcined at 600°C for 4.5h-5.5h to obtain an Al2O3-ZrO2 composite carrier;
[0070] Example 2
[0071] A method for preparing an Al2O3-ZrO2 composite carrier comprises the following steps:
[0072] (1) Weigh 73.5838 g aluminum nitrate nonahydrate, 13.0762 g zirconium oxychloride octahydrate, 11 g template, 10 ml PEG400, 20 g PEG2000, and 100 ml ethanol, dissolve in 400 ml distilled water, and stir magnetically for about 70 min to prepare a composite solution;
[0073] (2) Using NH3·H2O as a precipitant, slowly titrate NH3·H2O into the composite solution and continue stirring until the pH reaches 8.5 to obtain a white precipitate;
[0074] (3) Continue stirring for 140 min and then let stand and age for 19 h;
[0075] (4) The precipitate was centrifuged and filtered and washed four times with distilled water and ethanol respectively until no chloride ions could be detected with silver nitrate;
[0076] (5) Dry the obtained precipitate in a drying oven at 90°C for 14 h, then adjust the temperature to 130°C and continue drying for 14 h;
[0077] (6) After drying, the obtained solid was crushed, transferred to a muffle furnace, heated to 400°C at a heating rate of 1.1°C / min, and calcined for 140 min, followed by calcination at 600°C for 4.5h-5.5h to obtain an Al2O3-ZrO2 composite carrier;
[0078] Example 3
[0079] A method for preparing an Al2O3-ZrO2 composite carrier comprises the following steps:
[0080] (1) Weigh 73.5838 g aluminum nitrate nonahydrate, 13.0762 g zirconium oxychloride octahydrate, 11 g template, 10 ml PEG400, 20 g PEG2000, and 100 ml ethanol, dissolve in 400 ml distilled water, and stir magnetically for about 60 min to prepare a composite solution;
[0081] (2) Using NH3.H2O as a precipitant, slowly titrate NH3.H2O into the composite solution and continue stirring until the pH reaches 8 to obtain a white precipitate;
[0082] (3) Continue stirring for 120 min and then let stand and age for 12 h;
[0083] (4) The precipitate was centrifuged and filtered and washed three times with distilled water and ethanol respectively until no chloride ions could be detected with silver nitrate;
[0084] (5) Dry the obtained precipitate in a drying oven at 80°C for 12 h, then adjust the temperature to 120°C and continue drying for 12 h;
[0085] (6) After drying, the obtained solid was crushed, transferred to a muffle furnace, heated to 350°C at a heating rate of 1.0°C / min, and calcined for 120 min, followed by calcination at 600°C for 5 h to obtain an Al2O3-ZrO2 composite oxide;
[0086] Example 4
[0087] A method for preparing a nickel-based catalyst for methanation of carbon monoxide and carbon dioxide comprises the following steps:
[0088] Step 2: Preparation of finished carbon dioxide methanation catalyst:
[0089] (1) Weigh 0.9733 g of nickel nitrate hexahydrate, add it to 2.0 ml of distilled water and stir until it is completely dissolved to prepare a nickel nitrate solution;
[0090] (2) Weigh 0.75 g of the Al2O3-ZrO2 composite carrier prepared in Example 3 and add it to the nickel nitrate solution. Mix well and let stand for 5.5 h.
[0091] (3) The obtained sample was dried in a drying oven at 100°C for 10 h, and then heated to 600°C in a muffle furnace at a heating rate of 0.9°C / min and calcined for 4.5 h to obtain a finished carbon dioxide methanation catalyst, which was recorded as N / AZ600.
[0092] Moreover, N / AZ600 includes an active component and a carrier, wherein the active component is Ni, and the carrier is the Al2O3-ZrO2 composite oxide prepared in Example 3, wherein the mass percentage content of the active component in terms of NiO is 25wt%, and the rest is the carrier.
[0093] Moreover, the mass ratio of Al2O3 to ZrO2 in the Al2O3-ZrO2 composite carrier is 2:1.
[0094] Example 5
[0095] A method for preparing a nickel-based catalyst for methanation of carbon monoxide and carbon dioxide comprises the following steps:
[0096] Step 1: Preparation of Al2O3-ZrO2 composite carrier:
[0097] (1) Weigh 0.9733 g of nickel nitrate hexahydrate, add it to 2.0 ml of distilled water and stir until it is completely dissolved to prepare a nickel nitrate solution;
[0098] (2) Weigh 0.75 g of the Al2O3-ZrO2 composite carrier prepared in Example 3 and add it to the nickel nitrate solution. Mix well and let stand for 6.5 hours.
[0099] (3) The obtained sample was dried in a drying oven at 120°C for 14 h, and then heated to 800°C in a muffle furnace at a heating rate of 1.1°C / min and calcined for 5.5 h to obtain a finished carbon dioxide methanation catalyst, which was recorded as N / AZ800.
[0100] Moreover, N / AZ800 includes an active component and a carrier, the active component is Ni, the carrier is an amorphous aluminum-zirconium composite oxide, the amorphous aluminum-zirconium composite oxide is the Al2O3-ZrO2 composite carrier prepared in Example 3, the mass percentage content of the active component in terms of NiO is 25wt%, and the rest is the carrier.
[0101] Moreover, the mass ratio of Al2O3 to ZrO2 in the Al2O3-ZrO2 composite carrier is 2:1.
[0102] Example 6
[0103] A method for preparing a nickel-based catalyst for methanation of carbon monoxide and carbon dioxide comprises the following steps:
[0104] (1) Weigh 0.9733 g of nickel nitrate hexahydrate, add it to 2.0 ml of distilled water and stir until it is completely dissolved to prepare a nickel nitrate solution;
[0105] (2) Weigh 0.75 g of the Al2O3-ZrO2 composite carrier prepared in Example 3 and add it to the nickel nitrate solution. Mix well and let stand for 6 hours.
[0106] (3) The obtained sample was dried in a drying oven at 110°C for 12 h, and then heated to 700°C in a muffle furnace at a heating rate of 1.0°C / min and calcined for 5 h to obtain a methanation catalyst product, which was recorded as N / AZ700.
[0107] Moreover, N / AZ700 includes an active component and a carrier, the active component is Ni, the carrier is an amorphous aluminum-zirconium composite oxide, the amorphous aluminum-zirconium composite oxide is the Al2O3-ZrO2 composite carrier prepared in Example 3, the mass percentage content of the active component in terms of NiO is 25wt%, and the rest is the carrier.
[0108] Moreover, the mass ratio of Al2O3 to ZrO2 in the Al2O3-ZrO2 composite carrier is 2:1.
[0109] Comparative Example 1
[0110] In the preparation of the finished methanation catalyst of this comparative example, except that the obtained sample was dried in a drying oven at 110°C for 12 hours, and then heated to 500°C in a muffle furnace at a heating rate of 1.0°C / min and then calcined for 5 hours, the rest was the same as Example 6. The specific details are shown in Table 1.
[0111] Comparative Example 2
[0112] In the preparation of the finished methanation catalyst of this comparative example, except that the obtained sample was dried in a drying oven at 110°C for 12 hours, and then heated to 900°C in a muffle furnace at a heating rate of 1.0°C / min and then calcined for 5 hours, everything else was the same as Example 6. The specific details are shown in Table 1.
[0113] Table 1 Effect of temperature on catalyst
[0114] Serial number Calcination temperature (℃) <![CDATA[CO2 conversion rate (%)]]> <![CDATA[CH 4 Optional]]> Example 4 600 87.2 100 Example 5 800 87.1 100 Example 6 700 87.3 100 Comparative Example 1 500 75.9 91 Comparative Example 2 900 74.8 90
[0115] It can be seen from Table 1 that, using the catalyst prepared by the present invention, the CO2 conversion rate reaches 87.3, and the CH4 selectivity can reach 100%. The sintering temperatures of Comparative Examples 2 and 3 are 500°C and 900°C, respectively, and the CO2 conversion rates are 75.9% and 74.8%, respectively, and the CH4 selectivities are 91% and 90%, respectively. It can be proved that a sintering temperature that is too high or too low is not conducive to the performance of the methanation catalyst, and the sintering temperature adopted by the present invention is the optimal temperature.
[0116] Experimental Section
[0117] Experiment 1
[0118] The carrier prepared in Example 3 and the catalysts prepared in Examples 4-6 were characterized by EDX, XRD and HAADF-STEM. Figure 1-4 , Fig. 9 , Fig.13 shown.
[0119] from Figure 1 See on:
[0120] Example 3 The carrier exists in an amorphous state;
[0121] The Ni in Example 4 exists in the form of NiO;
[0122] In Example 6, Ni exists in the form of nickel aluminum spinel, but contains trace amounts of NiO;
[0123] In Example 5, Ni exists in the state of nickel aluminum spinel, but the carrier undergoes phase separation, and it is seen that Ni ions gradually combine with Al ions to form strongly interacting NiAl2O4;
[0124] from Figure 2 It can be seen that: the catalyst exists in an amorphous state;
[0125] from Figure 3 See: Ni is combined with Al, with high dispersion;
[0126] from Figure 4It can be seen that zirconium oxide and aluminum oxide are aggregated.
[0127] from Fig. 9 You can see:
[0128] In (a1), the amorphous state of N / AZ600 can be seen, in (a4, a5), the Al and Zr elements are evenly distributed, and in (a6), the Ni element is distributed over a large area, but some Ni clusters are interconnected.
[0129] In (b1), we can see that N / AZ700 has an obvious crystallization state and the nickel particles are evenly dispersed. In (b2), the sample surface is basically covered by Al and Ni elements, which confirms that the N / AZ700 catalyst exists in the form of "NiAl2O4 / ZrO2". In addition, we can see that Ni elements are mostly distributed in or around areas with higher Al concentrations, which confirms that Ni is easier to combine with Al. In (b3), we can see that the concentration of Ni element clusters increases and is independent of each other, and the dispersion is improved. In (b4, b5), we can see that the concentrations of Al and Zr elements change, which should be caused by the redispersion of various elements during the calcination process.
[0130] In (c1), we can see that the crystal state of the N / AZ800 sample is more obvious. In (c2), we can see that there are more Ni and Al elements exposed on the sample surface, and Ni is also concentrated in or around the area with high Al concentration. In (c5), we can see that the Zr element has obvious aggregation phenomenon, which is caused by the crystal phase transformation of ZrO2 during the roasting process.
[0131] Fig. 9 It is proved that changing the calcination temperature can change the distribution state of each element, thereby changing the carrier-metal interface in the catalyst.
[0132] from Fig.13 You can see:
[0133] The Ni element is mainly concentrated in the area with high Al concentration, while the Zr element is evenly distributed (f), indicating that the Ni in the N / AZ700 catalyst in the form of NiAl2O4 / ZrO2 still maintains its bond with Al. From (e), it can be seen that the nickel particles are aggregated, indicating that sintering occurs during the reaction process. However, no similar sintering phenomenon is found in Ni outside the area with high Al concentration, indicating that the Al-Zr-O interface can effectively hinder the sintering of nickel.
[0134] Experiment 2
[0135] The samples obtained in Examples 4-6 were tested for carbon dioxide methanation activity, and the specific research method is as follows:
[0136] The evaluation of the catalytic activity of carbon dioxide methanation was carried out on the SP-2100 chromatograph of Beijing Huarui Technology Co., Ltd. The raw gas was a mixture of carbon dioxide, hydrogen and argon (CO2:H2:Ar=15%:60%:25%).
[0137] Weigh 0.2g of catalyst and load it into a fixed bed reactor. Now reduce it at 700℃ for 2h in a hydrogen atmosphere with a hydrogen flow rate of 50ml / min. After the reduction is completed, continue to cool it in a hydrogen atmosphere. After it drops below 150℃, switch to raw gas with a gas flow rate of 50ml / min. The test temperature is 200-500℃. The gas after the reaction is discharged through a pipeline in one way and enters the chromatogram in the other way for online analysis. The gas is separated by a chromatographic column, and the reactants and products are detected by TCD. The conversion rate of the experimental results is as follows: Figure 5 As shown:
[0138] The catalyst prepared in Example 6 has a conversion rate of 87% at 400°C.
[0139] The highest conversion rates of Example 4 and Example 5 reach 86% and 80% at 400°C and 450°C, respectively.
[0140] Selectivity Figure 6 As shown:
[0141] The CH4 selectivity of Example 6 can be maintained at 100% before 450°C, showing excellent high-temperature selectivity.
[0142] The 138h long-term stability test results of Example 6 are as follows: Figure 7 As shown:
[0143] After rigorous high-temperature testing at 600°C, it can still maintain a carbon dioxide conversion rate of more than 75% and a CH4 selectivity of more than 98%.
[0144] The TG-DTG graph of the stability of the sample prepared in Example 6 is as follows: Figure 8 As shown:
[0145] from Figure 8 It can be seen that the amount of carbon deposits is very small, which indicates that the catalyst has good resistance to carbon deposits.
[0146] Experiment 3
[0147] The inventors compared the representative excellent catalysts developed in recent years with the catalyst of the present invention (Example 6). The specific experimental methods refer to the following literature, and the experimental results are shown in Table 2 and Fig.10 , Fig.11 shown.
[0148] Table 2 Comparison of other catalysts with the catalyst of the present invention
[0149]
[0150] It can be seen from Table 2 that at 3.0 MPa and air velocity of 15000 ml∙g −1 ∙h −1 Under the conditions of a temperature of 400°C, the CO2 conversion rate reaches 87.3% and the selectivity reaches 100%, which is significantly improved compared with other catalysts. This shows that the catalyst prepared by the technical solution of the present invention has high CO2 activity and good selectivity at high temperature.
[0151] Experiment 4
[0152] The catalyst prepared in the present invention (Example 6) was heated at 3.0 MPa and a space velocity of 15000 ml∙g −1 ∙h −1 The CO methanation reaction was carried out under the conditions of CO conversion and CH4 selectivity. Fig.14 , Fig.15 As shown in the figure: both CO conversion and CH4 selectivity increase with increasing temperature, and then begin to decrease due to thermodynamic limitations after reaching the maximum value; the N / AZ700 catalyst has a CO conversion of 99% and a CH4 selectivity of 100% at 350°C, showing high CO methanation activity; the multi-interface system catalyst prepared by calcination temperature-induced phase change shows excellent activity for both CO and CO2 methanation.
Claims
1. A nickel-based catalyst for the methanation of carbon monoxide and carbon dioxide, characterized in that: The nickel-based catalyst is a Ni-NiAl2O4 / Al2O3-ZrO2 catalyst; the catalyst comprises an active component and a carrier, the active component is Ni, the carrier is an amorphous aluminum-zirconium composite oxide, the mass percentage content of the active component in terms of NiO is 25wt%, and the rest is the carrier; the amorphous aluminum-zirconium composite oxide is an Al2O3-ZrO2 composite carrier; The mass ratio of Al2O3 to ZrO2 in the Al2O3-ZrO2 composite carrier is 2:1; The preparation method of the nickel-based catalyst is as follows: Step 1: Preparation of Al2O3-ZrO2 composite carrier: (1) Weigh 73.5838 g aluminum nitrate nonahydrate, 13.0762 g zirconium oxychloride octahydrate, 11 g template, 10 ml PEG400, 20 g PEG2000, and 100 ml ethanol, dissolve in 400 ml distilled water, and stir magnetically for 60 min to prepare a composite solution; (2) Using NH3·H2O as a precipitant, slowly titrate NH3·H2O into the composite solution and continue stirring until the pH reaches 8 to obtain a white precipitate; (3) Continue stirring for 120 min and then let stand and age for 12 h; (4) The precipitate was centrifuged and filtered and washed with distilled water and ethanol successively until no chloride ions could be detected with silver nitrate; (5) Dry the precipitate at 80°C for 12 h, then adjust the temperature to 120°C and continue drying for 12 h; (6) The solid obtained after drying was crushed, heated to 350°C at a heating rate of 1.0°C / min and calcined for 120 min, and then calcined at 600°C for 5 h to obtain an Al2O3-ZrO2 composite carrier; Step 2: Preparation of methanation catalyst product: (1) Weigh 0.9733 g of nickel nitrate hexahydrate, add it to 2.0 ml of distilled water and stir until it is completely dissolved to prepare a nickel nitrate solution; (2) Weigh 0.75 g of Al2O3-ZrO2 composite carrier and add it to nickel nitrate solution, mix well and let stand for 6 hours; (3) The obtained sample was dried at 110°C for 12 h, then heated to 700°C at a heating rate of 1.0°C / min and calcined for 5 h to obtain a finished methanation catalyst.
2. A nickel-based catalyst for methanation of carbon monoxide and carbon dioxide as claimed in claim 1, characterized in that: Aluminum nitrate nonahydrate, zirconium oxychloride octahydrate, and nickel nitrate hexahydrate were all analytical grade.
3. A nickel-based catalyst for methanation of carbon monoxide and carbon dioxide as claimed in claim 1, characterized in that: NH3·H2O was used as a precipitant and NH3·H2O was slowly titrated into the composite solution, which was kept in a 70°C water bath and stirred at a rate of 800 r / min.